Biological activity of Schinus molle on Triatoma infestans - Ferrero, Adriana Alicia (2006)
Hexanic extracts from leaves and fruits of Schinus molle were tested for repellent and insecticidal properties against first instar nymphs and eggs of Triatoma infestans, the vector of Chagas' disease. Leaf and fruit extracts were highly repellent for first nymphs. Fruit extracts had also ovicidal activity.